Investigation of work-related tension levels and related factors in healthcare workers - Çevik, Levent; Avcı, Dilek (Journal of Surgery and Medicine, 2021)
Background/Aim: Factors such as heavy workload and infectious diseases cause Work-Related Tension (WRT) in healthcare workers. This study aimed to evaluate the Work-Related Tension Scale (WRTS) scores of healthcare workers to assess whether they are concerned about infecting their families and themselves as a result of their work and whether they are thinking about being fired or changing professions if they have this anxiety. Methods: A total of 300 healthcare professionals working in a university hospital were included in this cross-sectional study. Data were obtained with the work-related stress scale (WRTS) and descriptive questionnaire and analyzed using SPSS 20.0 software. A P<0.05 was considered statistically significant. Descriptive statistics and ANOVA analysis were used during statistical evaluation. Results: The mean WRTS score (yes: 42.71) of the participants who had anxiety about infecting their families because of their jobs was significantly higher than that of the other groups (partially: 41.49, no: 38.16) (P<0.001). The mean WRTS score (yes: 42.27) of the participants who had anxiety about infecting themselves was significantly higher than those who did not (partially: 40.9, no: 38.21) (P=0.012). Healthcare workers who wanted to resign due to this concern had a considerably higher mean WRTS score (yes: 43.70) than those who wanted to keep working (partially: 42.93, no: 39.86) (P<0.001). Conclusion: Healthcare workers are concerned about infecting themselves and their families because of their jobs. As a result of this concern, their WRT levels are increased, and they are alienated from their work. Measures to increase effective protection against infectious diseases and stress management are needed.